Impact of Tabata Training Under Digital Monitoring on Physical Fitness in High-Level University Tennis Athletes - Luo, YunZhong; Deng, Liang; Chen, Kai; Huang, XiaoLing (Quality in Sport, 2024)
Background: The increasing demand for improved physical conditioning in university tennis athletes has highlighted the need for training methods that effectively enhance endurance, explosiveness, and agility. Chinese university tennis players often face constraints such as limited training time and insufficient focus on physical conditioning, which adversely affect their competitive performance. This study investigates the impact of Tabata training under digital monitoring on the physical fitness of high-level university tennis athletes, offering novel insights into optimizing training efficacy. Methods: This experimental study involved 20 university tennis athletes who participated in an 8-week training intervention. The experimental group underwent Tabata training, while the control group adhered to traditional training methods. Both groups were assessed before and after the intervention on 11 physical fitness parameters, including strength, speed, agility, and endurance. Data were analyzed using SPSS, with paired t-tests conducted to examine changes in performance. Results: a. Speed: The experimental group exhibited significant improvements in the 20-meter sprint (P < 0.05), with no significant differences in the 5-meter and 10-meter sprints (P > 0.05). b. Strength: Significant improvements were observed across all strength parameters except for half-squat at half-body weight (P < 0.05). c. Agility: The experimental group showed highly significant improvements in agility (P < 0.001). d. Endurance: The experimental group demonstrated a highly significant increase in endurance (P < 0.001). Conclusion: An 8-week regimen of Tabata training significantly enhanced the physical performance of high-level university tennis athletes, particularly in agility and endurance. These findings affirm the effectiveness of Tabata training in improving athletic fitness.